Regulating the valence level arrangement of high-Al-content AlGaN quantum wells using additional potentials with Mg doping. Issue 9 (16th February 2022) - Lu, Shiqiang; Zheng, Tongchang; Jiang, Ke; Sun, Xiaojuan; Li, Dabing; Chen, Hangyang; Li, Jinchai; Zhou, Yinghui; Cai, Duanjun; Li, Shuping; Lin, Wei; Kang, Junyong
Abstract : Additional potentials, including Coulomb interaction as well as orbital state coupling induced by Mg doping, are proposed to regulate the valence level arrangement of AlN/Al0.75 Ga0.25 N quantum wells. Abstract : Quantum states and arrangement of valence levels determine most of the electronic and optical properties of semiconductors. Since the crystal field split-off hole (CH) band is the top valence band in high-Al-content AlGaN, TM-polarized optical anisotropy has become the limiting factor for efficient deep-ultraviolet (DUV) light emission. Additional potentials, including on-site Coulomb interaction and orbital state coupling induced by magnesium (Mg) doping, are proposed in this work to regulate the valence level arrangement of AlN/Al0.75 Ga0.25 N quantum wells (QWs). Diverse responses of valence quantum states |p i 〉 ( i = x, y, or z ) of AlGaN to additional potentials due to different configurations and interactions of orbitals revealed by first-principles simulations are understood in terms of the linear combination of atomic orbital states. A positive charge and large Mg dopant in QWs introduce an additional Coulomb potential and modulate the orbital coupling distance. For the CH band (p z orbital), the Mg-induced Coulomb potential compensates the orbital coupling energy. Meanwhile, the heavy/light hole (HH/LH) bands (p x and p y orbitals) are elevated by the Mg-induced Coulomb potential. Consequently, HH/LH energy levels are relatively shifted upward and replace the CH level to be the top of the valence band. The inversion of optical anisotropy and enhancement of TE-polarized emission are further confirmed experimentally via spectroscopic ellipsometry.